Mapping Students’ Development in Response to Sustainability Education: A Conceptual Model - Greig, Alison; Priddle, Julian (Sustainability, 2019)
Target 4.7 of the Sustainable Development Goals requires that, by 2030, all learners acquire the knowledge and skills needed to promote sustainable development. This not only demands an interdisciplinary approach, but also that this approach must seek to be transformative, with change for sustainability as an explicit outcome in addition to subject knowledge. Many have argued that the complex or ‘wicked’ nature of sustainability challenges indicates the need for a learning experience that emphasizes active, reflective learning across-and between-discipline areas. In this paper we develop a conceptual model of sustainability learning for higher education that can potentially address the distinctiveness of sustainability education and monitor students’ progression as learners. Our conceptual model of sustainability learning, has been developed on a university Master’s program in Sustainability and integrates continua of pedagogy and disciplinarity into a three-dimensional space. Learners can be represented as different loci within this space at different points in their development. This potentially allows a ‘learning journey’ to be plotted. We propose that the model can also be used more widely as a tool to visualize learning progression within other university programs, providing an opportunity for both learners and curriculum designers to reflect on progress.